FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN IMUNISASI TETANUS TOXOID PADA IBU HAMIL - Rahmadani Putri; Merisa Riski; Syarifah Ismed; Titin Dewi Sartika Silaban (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Tetanus neonatorum is caused by Clostridium Tatami toxin. The study aimed to determine the factors associated with the completeness of tetanus toxoid immunization for pregnant women. This type of research is quantitative, and analytic with a cross-sectional approach. The sample was selected by systematic random sampling so that a sample of 75 pregnant women was obtained. The completeness of tetanus toxoid immunization were measured using a questionnaire. The results of the Chi-Square test of attitudes toward the completeness of tetanus toxoid immunization showed that there was no relationship between the attitudes of pregnant women and completeness of tetanus toxoid immunization with a p-value = 0.466 < 0.05 and the relationship between education and completeness of tetanus toxoid immunization, p-value = 0.000 < 0.05, knowledge with the completeness of tetanus toxoid immunization with p-value = 0.000 < 0.05, occupation with the completeness of tetanus toxoid immunization with p-value = 0.000 < 0.05, and husband's support with the completeness of tetanus toxoid immunization with p-value = 0.311 < 0.05 which means no relationship. The conclusion is that there is a relationship between education, knowledge, and work with the completeness of tetanus toxoid immunization, and there is no relationship between attitudes and husband's support for the completeness of tetanus toxoid immunization for pregnant women in the work area of ??the Puskesmas in Ogan Ilir Regency. Suggestions to the Puskesmas It is hoped that it can improve the quality of public health services, especially for pregnant women, can provide information on the importance of tetanus toxoid immunization for pregnant women to overcome pregnant women who have not been fully immunized to achieve the target of tetanus toxoid immunization to reduce morbidity and mortality in maternity and newborn baby.